Numerical Study of Gravity Dam with Gallery Study under Influence of Sloshing Wave Using ANSYS.16: A Numerical Study of Stress Analysis and Wave Influence on a Gravity Dam with Gallery using ANSYS.16 (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Drainage gallery is very critical in case of gravity dam. Numerical three-dimensional FEA flow analysis is a very efficient method for the stress analysis of the subsurface drainage systems of concrete gravity dams. The gravity method of the analysis does not consider the size of opening and the elastic property of dam material. Thus the objective of study is comprises of the Finite Element Method which considers the size of opening, elastic property of material, and stress distribution because of geometric discontinuity in cross section of dam. The pressure due to wave also plays important role on dam wall. This paper deals with the study of stresses analysis of koyna dam of 103.00m high above ground level with varying thickness in accordance with IS 6512. This dam has been analyzed for different types of load using ANSYS software by assuming fixity at the base. The analysis of dam structure has been carried out using 8 noded SHELL 181 elements with uniform SHELL thicknesses